2018
DOI: 10.3390/su10103366
|View full text |Cite
|
Sign up to set email alerts
|

Critical Thinking Development—A Necessary Step in Higher Education Transformation towards Sustainability

Abstract: Education for sustainable development has been addressed by professionals, authorities, and a number of research studies in the last decades, and yet the results are not clearly visible. Teachers as agents of a new mindset do not seem to understand the ways of approaching raising awareness of the issues of global challenges. This study investigated the possibility of raising the extent of applying critical thinking to the problem-solving issues of a group of student teachers in their initial training. The samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(76 citation statements)
references
References 30 publications
0
66
0
10
Order By: Relevance
“…Empirical studies have shown that critical thinking in students can be developed using student-based learning strategies and having them face everyday problems that require approaches to reasoning that allow them to construct new knowledge, based on the mindsets they already have [8,[44][45][46]. Thus, by facilitating the planning, adaptation, and reflection used to solve the problems posed, business simulations constitute an adequate tool for students to construct knowledge and therefore represent an element that facilitates the development of critical thinking [7,[47][48][49][50].…”
Section: Higher Education and Critical Thinkingmentioning
confidence: 99%
“…Empirical studies have shown that critical thinking in students can be developed using student-based learning strategies and having them face everyday problems that require approaches to reasoning that allow them to construct new knowledge, based on the mindsets they already have [8,[44][45][46]. Thus, by facilitating the planning, adaptation, and reflection used to solve the problems posed, business simulations constitute an adequate tool for students to construct knowledge and therefore represent an element that facilitates the development of critical thinking [7,[47][48][49][50].…”
Section: Higher Education and Critical Thinkingmentioning
confidence: 99%
“…One of the central premises for the development of ESD is access to education and the individuals' capacity to engage in training and learning, for the purpose of developing skills such as: anticipation, interdisciplinarity, diversity of perspectives, working with incomplete or complex information, participation in sustainable development processes, cooperation, individual decision-making capacities, empathy, solidarity, and self-motivation [31,34,35]. Given that self-organising, self-determination and project-based work capacities are essential in forming these skills, the employees' training becomes an on-going need [36].…”
Section: Education For Sustainable Developmentmentioning
confidence: 99%
“…Therefore, collaborative and problem-oriented approaches may be essential to the implementation of sustainable development and education [1]. Education, therefore, calls for transdisciplinary knowledge and skills in collaborative problem-solving (CPS), whereby students build and integrate their and others' knowledge across disciplines and apply transdisciplinary knowledge to real community problems [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, people have to work together and use different information collection strategies to tackle problems. Consequently, an individual has to be supported by others to be able to complete sophisticated tasks [3].…”
Section: Introductionmentioning
confidence: 99%